Lagak Jakarta / Benny Rachmadi, Muhammad Misrad; editor, Candra Gautama, Pax Benedanto - BENNY RACHMADI; Muhammad Misrad; Candra Gautama; Pax Benedanto (KPG (Kepustakaan Populer Gramedia), 2008)
... jilid : ilus. ; 16 x 24 cm.